STRENGTHENING ACCOUNTABILITY IN INDONESIAN NOTARIAL PRACTICE: THE LEGAL GAP ON LIABILITY FOR BACKDATED DEEDS - Zahwa Maulidina Afwija; Yeni Oktafia; Abdul Ghofar (Indonesia Private Law Review, 2025)
The issuance of backdated deeds raises serious legal concerns as it can misrepresent facts and violate procedural requirements under Indonesian notarial law. Although a notarial deed’s formal validity relies on its authenticity, backdating undermines this integrity and may result in significant legal consequences. Law Number 30 of 2004 concerning the Notary Profession (UUJN) and its amendments do not explicitly regulate notary liability toward third parties who suffer losses, creating a normative gap and weakening legal protection. This study examines the legal implications of backdated deeds and the scope of notary liability using a normative juridical approach with statutory and conceptual analyses, focusing on the interrelation of administrative, civil, and criminal responsibilities. Findings indicate that a notary may face administrative sanctions under Articles 12 and 65A UUJN, civil liability under Articles 1243 and 1365 KUHPerdata, and criminal sanctions under Articles 263 and 264 KUHAP. These results underscore the need for regulatory reform to ensure accountability and strengthen legal certainty, and the study recommends enhancing notarial prudence and ethical compliance, reinforcing supervisory oversight, and revising notarial law to provide explicit sanctions and protection for parties harmed by backdated deeds.